Hubungan Intensitas Penggunaan Gadget dengan Risiko Masalah Perilaku Emosional Anak - Seif Firinda; Ahmad Suryawan; Linda Dewanti; Astika Gita Ningrum (Malahayati Nursing Journal, 2024)
ABSTRACT Gadgets are technological developments that can make users dependent, including preschool children. Gadgets are a type of technology that is in great demand among various groups, from adults to teenagers and even young children who use gadgets. Excessive use of gadgets can cause health problems for users, including impaired concentration in learning, impaired child development, sleep disturbances, impaired vision, hearing and disruption of social interaction with the surrounding environment. When using gadgets, children become less interactive and communicate less. The child's development period is very sensitive when the child is 1-5 years old, because at this time the child experiences the golden age. Social emotional processes involve changes in relationships with other people, namely changes in emotions and personality. To identify the intensity of gadget use and children's emotional behavior and analyze the relationship between the two. This research is an observational analytic with a cross sectional study. The total sample was 112 children with the sampling technique being total sampling. The independent variable is the intensity of gadget use which is measured using a questionnaire. The dependent variable is the risk of children's emotional behavior problems as measured by the Emotional Behavior Problems Questionnaire (KMPE). Data analysis used the Spearman test. Almost half of the respondents had a high category of gadget usage intensity, and most of the respondents had emotional behavior problems in the high category. The Spearman test results obtained a p value of 0.001 with a coefficient value of 0.312. There is a sufficient and unidirectional relationship between the intensity of gadget use and the risk of children's emotional behavior problems at Aisyiyah Bustanul Athfal 10 Gresik Kindergarten. It can be interpreted that the higher the intensity of gadget use, the greater the chance that a child will have a risk of emotional behavior problems in the reconciliation category. Keywords: Gadgets, Children Emotional Behavior, Preschoolers  ABSTRAK Gadget merupakan perkembangan teknologi yang dapat membuat penggunanya menjadi ketergantungan, termasuk anak prasekolah. Gadget salah satu teknologi yang banyak diminati di berbagai kalangan, mulai dari kalangan dewasa remaja bahkan anak usia dini sudah menggunakan gadget. Pengguanan gadget secara berlebihan dapat menimbulkan masalah kesehatan bagi penggunanya diantaranya gangguan konsentrasi belajar, gangguan perkembangan anak, gangguan tidur, gangguan penglihatan, pendengaran dan gangguan terhadap interaksi sosial dengan lingkungan sekitar. Ketika menggunakan gadget, anak menjadi kurang berinteraksi dan kurang berkomunikasi. Periode perkembangan anak sangat sensitif saat anak berusia 1-5 tahun, karena pada masa ini anak mengalami masa golden age atau masa emas. Proses sosial emosi melibatkan perubahan dalam hubungan orang lain, yaitu perubahan emosi dan kepribadian.   Untuk mengidentikfikasi intensitas penggunaan gadget dan perilaku emosional anak serta menganalisis hubunbgan diantara keduanya. Penelitian ini merupakan analitik observasional dengan studi cross sectional. Jumlah sample sebanyak 112 anak dengan teknik pengambilan sampel adalah total sampling. Variabel bebas adalah intensitas penggunaan gadget yang diukur menggunakan kuesioner. Variabel terikatnya adalah risiko masalah perilaku emosional anak yang diukur dengan Kuesioner Masalah Perilaku Emosioanal (KMPE). Analisis data menggunakan uji Spearman. Hampir separuh responden memiliki intenistas penggunaan gadget kategori tinggi, dan sebagian besar responden memiliki masalah perilaku emosional dalam kategori tinggi. Hasil uji Spearman didaptkan nilai p value 0,001 dengan nilai koefisiensi 0,312. Terdapat hubungan yang cukup dan searah antara intensitas pengggunaan gadget dengan risiko masalah perilaku emosional anak di TK Aisyiyah Bustanul Athfal 10 Gresik. Dapat diartikan bahwa semakin tinggi intensitas penggunaan gadget semakin meningkatkan peluang anak memiliki risiko masalah perilaku emosional dengan kategori rujuk Kata Kunci: Gadget, Perilaku Emosional Anak, Anak Prasekolah